Clinical trial of modulatory effects of oxytocin treatment on higher-order social cognition in autism spectrum disorder: a randomized, placebo-controlled, double-blind and crossover trial. Issue 1 (December 2016) - Preckel, Katrin; Kanske, Philipp; Singer, Tania; Paulus, Frieder; Krach, Sören
Abstract Background Autism spectrum disorders are neurodevelopmental conditions with severe impairments in social communication and interaction. Pioneering research suggests that oxytocin can improve motivation, cognition and attention to social cues in patients with autism spectrum disorder. The aim of this clinical trial is to characterize basic mechanisms of action of acute oxytocin treatment on neural levels and to relate these to changes in different levels of socio-affective and -cognitive functioning. Methods This clinical study is a randomized, double-blind, cross-over, placebo-controlled, multicenter functional magnetic resonance imaging study with two arms. A sample of 102 male autism spectrum disorder patients, diagnosed with Infantile Autistic Disorder (F84.0 according to ICD-10), Asperger Syndrome (F84.5 according to ICD-10), or Atypical Autism (F84.1 according to ICD-10) will be recruited and will receive oxytocin and placebo nasal spray on two different days. Autism spectrum disorder patients will be randomized to determine who receives oxytocin on the first and who on the second visit. Healthy control participants will be recruited and case-control matched to the autism spectrum disorder patients. The primary outcome will be neural network activity, measured with functional magnetic resonance imaging while participants perform socio-affective and -cognitive tasks. Behavioral markers such as theory of mind accuracy ratings and response times will be assessed as secondary outcomes in addition to physiological measures such as skin conductance. Trait measures for alexithymia, interpersonal reactivity, and social anxiety will also be evaluated. Additionally, we will analyze the effect of oxytocin receptor gene variants and how these potentially influence the primary and secondary outcome measures. Functional magnetic resonance imaging assessments will take place at two time points which will be scheduled at least two weeks apart to ensure a sufficient wash-out time after oxytocin treatment. The study has been approved by an ethical review board and the competent authority. Discussion Revealing the mechanisms of acute oxytocin administration, especially on the socio-affective and -cognitive domains at hand, will be a further step towards novel therapeutic interventions regarding autism. Trial registration German Clinical Trial RegisterDRKS00010053 . The trial was registered on the 8th of April 2016